Metagenomic analysis of mosquitoes from Kangerlussuaq, Greenland reveals a unique virome - Mirjam Schilling; Madhujot Jagdev; Huw Thomas; Nicholas Johnson (Scientific Reports)
Abstract Climate change is dramatically affecting vector ecology in extreme environments such as the Arctic. However, little is known about the current status of viruses of arthropod vectors located in such northerly locations. As part of a field survey on the role of wildlife in international movement of zoonotic pathogens, we sampled mammalophilic mosquitoes near the settlement of Kangerlussuaq, Greenland in July 2022 and July 2023 to investigate their virome. The majority of mosquitoes were identified as either Aedes impiger or Aedes nigripes. Metagenomic analysis of RNA extracted from species pools detected a number of novel RNA viruses belonging to a range of different virus families, including Flaviviridae, Orthomyxoviridae, Bunyavirales, Totiviridae and Rhabdoviridae. However, the sequence identities when compared to previously published, were as low as 34% at the amino acid level. Furthermore, a comparison of virome diversity between Aedes species emphasises the uniqueness of both Aedes impiger and Aedes nigripes from this secluded ecosystem. It also highlights the need to better understand the viromes of potential pathogen vectors as the impacts of climate change are experienced in such northerly ecosystems.